Phraseology as a means of moral values of Russian national personality reflection - Kovalenko E. G. (Interactive science, 2016)
the article deals with the peculiarities of linguistic personality; examines the ideographic groups of phraseological units, an integral semantics of which reflects the most important semantic dominants of the concept of Russian national personality; restores on the basis of phraseology of the moral sphere of human the positive type (portrait) of Russian national personality.
Keywords: языковая личность; русская национальная личность; фразеология моральной сферы человека; культурные доминанты; интегральная семантика; linguistic personality; cultural dominance; integral semantics; Russian national personality; phraseology of a moral sphere of the human